The Evolution of the Classification of Psychiatric Disorders - Surís, Alina (Behav Sci (Basel), 2016)
This article traces the history of classification systems for mental illness and then reviews the history of the American diagnostic system for mental disorders. The steps leading up to each publication of the Diagnostic and Statistical Manual (DSM) are described including leaders, timelines, pre-publication meetings, and field trials. Important changes in the purpose of the manuals are described with a focus on events leading to the manual’s third edition (DSM-III), which represented a paradigm shift in how we think about, and use, the classification system for mental illness. For the first time, DSM-III emphasized empirically-based, atheoretical and agnostic diagnostic criteria. New criticisms of the DSM-III and subsequent editions have arisen with a call for a new paradigm shift to replace diagnostic categories with continuous dimensional systems of classification, returning to etiologically-based definitions and incorporating findings from neurobiological science into systems of diagnosis. In the foreseeable future, however, psychiatric diagnosis must continue to be accomplished by taking a history and assessing the currently established criteria. This is necessary for communication about diseases and education of clinicians and scientists in medical fields, as well as advancement of research needed to further advance the diagnostic criteria of psychiatry.